Differences in the Values of the Senior Management Team, Antirisk Ability, and Innovation Performance by the Data-Driven Approach: Evidence from 841 Listed Companies in China - Guangyin Tong (Journal of Mathematics)
This study explores the mechanism of corporate antirisk capabilities on corporate innovation performance by using a data-driven method. The data are from China’s Shanghai and Shenzhen A-share listed companies from 2013 to 2018. The value differences between the senior management team’s ability to resist risk and innovation performance are discussed. The results show that the antirisk ability of an enterprise will improve the efficiency of the utilization of enterprise resources and promote the formation of competitive advantage so that enterprises have a more stable internal and external environment, so as to improve the innovation performance of the enterprise. Risk capability improves corporate innovation performance; from the perspective of the value difference of the senior management team, a smaller value difference has a more significant effect on enhancing the enterprise’s antirisk ability and improving corporate innovation performance than a larger value difference. While improving their own antirisk capabilities, companies should further promote and improve the consistency of senior management team values, thereby improving corporate innovation performance.